Effects of a Brief Hypnosis Relaxation Induction on Subjective Psychological States, Cardiac Vagal Activity, and Breathing Frequency. Issue 4 (2nd October 2018) - Laborde, Sylvain; Heuer, Sebastian; Mosley, Emma
Abstract: This study investigated the effects of a brief hypnosis including relaxation suggestions on physiological markers of relaxation, cardiac vagal activity, and breathing frequency. Forty participants were tested in a within-subjects design. Participants listened to a recorded hypnosis session and to a nonhypnotic recording. No differences were found regarding cardiac vagal activity. Participants breathed significantly faster during the audio conditions (hypnosis and nonhypnotic recording) in comparison to resting measures. After hypnosis, subjective arousal was significantly lower and emotional valence was significantly more positive than after the nonhypnotic recording condition. The relaxing effects of hypnosis that includes relaxation suggestions appear to be located at the subjective level but not at the peripheral physiological level.